The role of post-transcriptional regulation in SARS-CoV-2 infection and pathogenicity - Wang, Xuan; Chang, Zecheng; Zhao, Tingting; Zhong, Weiyao; Shi, Jingwei; Wang, Guoqing; Xu, Xuesong (Frontiers in Immunology, 2023)
The COVID-19 pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus has had a significant impact on global social and economic stability. To combat this, researchers have turned to omics approaches, particularly epitranscriptomics, to limit infection and develop effective therapeutic strategies. Multi-omics can provide the host response dynamics during multiple disease phases to reveal the molecular and cellular landscapes. Epitranscriptomics focuses on the mechanisms of gene transcription in cells and tissues and the relationship between genetic material and epigenetic regulation. This review highlights the role of post-transcriptional regulation in SARS-CoV-2, which affect various processes such as virus infection, replication, immunogenicity, and pathogenicity. The review also explains the formation mechanism of post-transcriptional modifications and how they can be regulated to combat viral infection and pathogenicity.